Standardized Patient Cases for Skill Building in Patient-Centered, Cross-Cultural Interviewing (Stanford Gap Cases) - Elizabeth Stuart; Sylvia Bereknyei; Michele Long; Rebecca Blankenburg; Valerie Weak; Ron Garcia (Association of American Medical Colleges, 2012)
Abstract This resource includes materials needed to run a 4-case standardized patient exercise in patient-centered, cross-cultural interviewing. The goal of the exercise is to enable participants to identify and bridge cultural gaps between patients and medical providers. The Gap Cases exercise was developed as a formative component of the core clerkship in pediatrics at the Stanford School of Medicine. Important features: The program emphasizes a patient-centered, individualized approach to cross-cultural interactions. In its original format, the exercise is run as a group session led by faculty facilitators, with students observing one another and giving feedback. Cases and related materials are easily adapted to different settings and target audiences, (e.g. informal role-plays, small or large group discussion with students, residents, and/or faculty). Cases are built from everyday experiences. Learning points can be readily practiced and reinforced in the context of routine clinical care. The materials submitted expand the body of case-based educational resources available for skill building in cross-cultural interviewing. Our program has been running continuously since 2006, with one group of 8 clerkship students participating each month. (~ 480 students over the past 5 years). To date, we have relied on student surveys to evaluate the effectiveness of the program. Students complete an anonymous, open-ended survey at the end of each Gap Cases session. (A copy of the questionnaire is included with the Session Tools set of resource files.) During the first year of the program we analyzed themes from 140 students' responses to the survey questions about key learning points and reactions to observing peers and being observed. Key learning points included: Importance of eliciting patients' perspectives (35%) Ideas for general interviewing (22%) Broader awareness of cultural issues (13%) Importance of social context (9%) Reactions to observing other students' interviews were 91% positive and otherwise mixed. Reactions to being observed by peers were 77% positive, 7% neutral or negative, and otherwise mixed. Students perceived peer feedback to be constructive and helpful in making them aware of blind spots. (See the Instructor's Guide for sample narrative comments from the student questionnaire.) Additional informal feedback from students indicates that having a faculty case facilitator - rather relying solely on standardized patients to provide feedback - is a valued feature of the program. During the first year of the program, students also completed a retrospective pre-post version of the Health Beliefs Attitudes Survey (HBAS, Dobbie 2002) at the end of each clerkship rotation. The HBAS measures perceived importance of understanding patients' perspectives on illness. We surveyed 52 students at the end of the clerkship during the initial year of the program; 85% completed surveys. Results showed small, but statistically significant attitudinal changes in the four domains measured by the instrument. Since the first year of the program we have continued to use the end-of-session qualitative evaluation form, with similar themes arising in students' responses.